Analisis Kemampuan Berpikir Matematis Siswa pada Pembelajaran Aritmatika Sosial Ditinjau dari Model Pembelajaran dan Self Efficacy Siswa - Nandang Arif Saefuloh; Wahyudin Wahyudin; Sufyani Prabawanto; Usep Kosasih; Samnur Saputra; Deti Ahmatika; Iden Rainal Ihsan (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2023)
The main problem in this study is students' ability to think mathematically in solving mathematical problems in learning social arithmetic in their class through minimum guidance-based learning (PBL and DL). This research uses a mixed method to look at the description of students' mathematical thinking abilities and the tendency of these abilities based on students' self-efficacy levels. The results showed that the increase in students' mathematical thinking skills at each level of low self-efficacy based on n-gain calculations. In addition, there is no significant difference in the scores for improving students' mathematical thinking skills based on the learning model and the level of self-efficacy. There is no significant interaction between the Learning Model and the Level of Self-efficacy in determining the increase in the average score of students' mathematical thinking abilities. Other findings show that students with low self-efficacy tend to have limitations in the ability to think mathematically in the process of conjecture and convincing. On the other hand, students with moderate and high self-efficacy have more complete mathematical thinking abilities, including specialization, generalization, conjecture, and convincing. However, in the process of conjecture and convincing, two sub-processes are found, namely knowledge modification using factual knowledge, contextual tools, or substantive thinking, as well as the process of selecting relevant information in solving problems. Therefore, the two groups are divided into four groups based on the way students use conjecture and convincing mathematical thinking abilities, namely: (1) students use specialization mathematical thinking skills based on the knowledge learned from the teacher, (2) students use specialization mathematical thinking abilities based on knowledge acquired in everyday life, (3) students use convincing mathematical thinking abilities by examining the formula used or based on knowledge learned from the teacher, and (4) students use convincing mathematical thinking abilities based on the knowledge obtained in everyday life (factual knowledge).